A distributed averaging-based evidential Expectation-Maximization algorithm for density estimation in unreliable sensor networks. (1st December 2020) - Safarinejadian, Behrouz; Mozaffari, Mohiyeddin
Highlights: A distributed algorithm for density estimation and data clustering. Minimizing the effects of uncertainties in sensor measurements. The proposed algorithm analytically converges to the maximum likelihood estimates. Abstract: In this paper, a novel distributed averaging-based evidential Expectation-Maximization algorithm is presented for data clustering and probability density function estimation in unreliable sensor networks in the presence of uncertain observations. All observations of the sensor network are statistically modelled by a Gaussian mixture model. A generalized likelihood function is maximized in a distributed manner for density estimation. For this purpose, the parameters of the mixture model such as weighting coefficients, mean vectors, and covariance matrices are updated by using a distributed averaging method. The proposed algorithm can be applied to any network with a mesh topology. The convergence of algorithm is also investigated and guaranteed by using a mathematical analysis. In the simulation result section, the proposed algorithm has been applied to a simulated uncertain sensor network with a mesh topology. The simulations confirm the favourable performance of the distributed averaging-based evidential EM algorithm.